Experimental study on bearing resistance of short displacement pile groups in dense sands - Norkus, Arnoldas; Martinkus, Vaidas (Journal of Civil Engineering and Management, 2019)
The prediction of the behavior of structures interacting with soil is one of the main challenges in structural design. Accurate evaluation of soil–structure interaction ensures a rational design solution for the superstructure and foundation of a building. In structural analysis, one of the key problems is the identification of relevant movements of the foundation considering the interaction between the superstructure, foundation and ground (the soil mass around the foundation). The correct assessment of soil–structure interaction contributes to the rational constructional design of the superstructure and foundation and allows avoiding violations of requirements for ultimate and serviceability limit states possible due to unpredicted additional stress on the structural system. Resistance predictions for pile group foundations is a complex problem, which may be the reason for scattered and insufficient information available despite numerous experimental and numerical studies, predominated by the focus on partial empirical relationships. This experimental study analyzed the prototype of a short displacement pile group with a flexible pile cap in terms of the bearing capacity and deformation behavior while subjected to static axial vertical load. In particular, attention was given to the resistance–stiffness evolution of single piles acting in a pile group with different spacing. Test results of short displacement pile groups were used to verify known models for the bearing resistance prediction of the pile group.